New Directions in Anthropological Kinship - Stone, Linda (Rowman & Littlefield Publishers, 2002)
Following periods of intense debate and eventual demise, kinship studies is now seeing a revival in anthropology. New Directions in Anthropological Kinship captures these recent trends and explores new avenues of inquiry in this re-emerging subfield. The book comprises contributions from primatology, evolutionary anthropology, archaeology, and cultural anthropology. The authors review the history of kinship in anthropology and its theory, and recent research in relation to new directions of anthropological study. Moving beyond the contentious debates of the past, the book covers feminist anthropology on kinship, the expansion of kinship into the areas of new reproductive technologies, recent kinship constructions in EuroAmerican societies, and the role of kinship in state politics.